THE ULTRAMARES CASE. (The Accounting Review, 1931)
Abstract In February, 1924, Messrs, Touche, Niven, & Co. audited for the fourth successive year books of one Fred Stern & Co. Inc., of New York, a rubber importer and dealer and prepared thirty-two copies of a balance sheet to which the following certificate, dated February 26, 1924, was affixed. According to the balance sheet, the net worth of the company was more than one million dollars. The Ultramares Corp., professedly relying upon the balance sheet, began to loan money to the Stern Company on trust receipts in March, 1924. Actually, the company was insolvent and the balance sheet false, in December of the same year the Stern Company collapsed. The Ultramares Corp. then sued Messrs, Touche, Niven, & Co. and in the appellate division of the New York State Supreme Court (I) secured judgment of $208,058.97 for damages arising out of the negligence of accountants but was unsuccessful in reinstituting a charge of fraud and collusion on the part of accountants' employees with Stern officials, which had been dismissed by the trial court. The case was then carried to the highest court of the state by both plaintiff and defendant. Judge Cardozo in an exceedingly able and trenchant opinion reversed both findings.